Diagnostic ability of linked color imaging in ultraslim endoscopy to identify neoplastic lesions in the upper gastrointestinal tract - Haruma, Ken; Kato, Mototsugu; Kawada, Kenro; Murao, Takahisa; Ono, Shoko; Suehiro, Mitsuhiko; Hori, Shinichiro; Sasaki, Fumisato; Koike, Tomoyuki; Kitamura, Shinji; Dohi, Osamu; Kanzaki, Hiromitsu; Yagi, Nobuaki; Hashiguchi, Keiichi; Oka, Shiro; Katada, Kazuhiro; Shimoda, Ryo; Mizukami, Kazuhiro; Takeuchi, Toshihisa; Katsuki, Shinichi; Tsuda, Momoko; Naito, Yuji; Kawano, Tatsuyuki; Mori, Keita; Ishikawa, Hideki (Endoscopy International Open, 2022)
Background and study aims Linked color imaging (LCI) is a new image-enhancing technique that facilitates the differentiation of slight differences in mucosal color tone. We performed an exploratory analysis to evaluate the diagnostic capability of LCI in ultraslim endoscopy, using data from patients examined in the LCI-Further Improving Neoplasm Detection in upper gastrointestinal (LCI-FIND) trial, a large-scale, multicenter, randomized controlled trial that demonstrated the capability of LCI for detecting neoplastic lesions in the upper gastrointestinal tract.Patients and methods Data from the LCI-FIND prospective trial were used. In the LCI-FIND trial, 1502 patients with a history of gastrointestinal cancer were randomly assigned to two groups based on examination methods: white light imaging (WLI) followed by LCI (WLI group) and LCI followed by WLI (LCI group). The present exploratory analysis investigated the outcomes of patients who underwent ultraslim and standard endoscopies.Results Ultraslim endoscopes were used in 223 patients and standard endoscopes in 1279 patients. The primary endpoint of the LCI-FIND trial was the percentage of patients diagnosed with a neoplastic lesion using WLI or LCI. The corresponding percentage tended to be higher with LCI than with WLI among patients who underwent ultraslim endoscopy and among those who underwent standard endoscopy; the crude risk ratio was 2.21 [95 % confidence interval (CI): 1.06–4.67], and the adjusted odds ratio was 2.46 (95 % CI: 1.07–5.63).Conclusions Our exploratory analysis of data from the LCI-FIND trial showed that LCI is useful in identifying neoplastic lesions, when used in ultraslim endoscopy.